2017
DOI: 10.1007/s13320-017-0404-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of photonic crystal fiber based sensor for gas condensate and air pollution monitoring

Abstract: Abstract:In this paper, a hexagonal shape photonic crystal fiber (H-PCF) has been proposed as a gas sensor of which both micro-structured core and cladding are organized by circular air cavities. The reported H-PCF has a single layer circular core which is surrounded by a five-layer hexagonal cladding. The overall pretending process of the H-PCF is completed by using a full vectorial finite element method (FEM) with perfectly matched layer (PML) boundary condition. All geometrical parameters like diameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The cross-section of these fibers has the characteristic periodic refractive index that serves to create the PBG (see Figure 3 a–c for some examples). These have been reported in an array of geometries for guidance of light from UV [ 135 ] to near-IR light [ 136 ] through media such as gases [ 137 ], liquids [ 138 ], and hydrogels [ 139 ]. While there are many sensing modalities that benefit from these fibers [ 140 ], in this review, we will focus on fluorescence detection and enhancement.…”
Section: Photonic Crystal Fibers (Pcfs) For Fluorescence-based Applic...mentioning
confidence: 99%
“…The cross-section of these fibers has the characteristic periodic refractive index that serves to create the PBG (see Figure 3 a–c for some examples). These have been reported in an array of geometries for guidance of light from UV [ 135 ] to near-IR light [ 136 ] through media such as gases [ 137 ], liquids [ 138 ], and hydrogels [ 139 ]. While there are many sensing modalities that benefit from these fibers [ 140 ], in this review, we will focus on fluorescence detection and enhancement.…”
Section: Photonic Crystal Fibers (Pcfs) For Fluorescence-based Applic...mentioning
confidence: 99%
“…Where, Aea is the effective area and intensity electric field is the I(e) = |Ee| 2 PF is indicated that the most amount of power flowing in the core area of the D-PCF structure.…”
Section: Mathematical Analysis Of Optical Propertiesmentioning
confidence: 99%
“…The gray area exists within the situation of ultraviolet radioactivity and the microwave range. The huge THz occurrence has applications in a variety of fields such as detection [1][2], biomedical tomography [3], transport network [4], bioengineering [5], time-domain spectrometry [6], brininess [7], infection sensor [8], security screening [9] applications. It also makes significant advances in the roots and documentation systems of the THz wave.…”
Section: Introductionmentioning
confidence: 99%
“…Tray area lies within the context of the infrared radiation (IR) and microwave spectrum. The enormous THz frequency is potential in diverse areas like sensing [1][2], biomedical imaging [3], communications [4], biotechnology [5], time-domain spectroscopy [6], salinity [], temperature sensor [7], security screening [8] applications. It also provides significant developments in origins and identification methods of THz wave.…”
Section: Introductionmentioning
confidence: 99%